Facility Layout Design Using From To Chart (FTC) Method and Automated Layout Design Program (ALDEP) - Rahayu, Ade Astuti Widi; Fathurohman, Fathurohman; Pratiwi, Rizki Amalia; Fariza, Amelia Nur (Center for Study and Journal Management FTI UMI, 2024)
This research is conducted in SMEs engaged in the convection of children's and adult clothing. The problems in this study related to the optimization of the layout of the facility. The study aims to determine and compare the distance of moving materials before and after designing the layout of the facility and determining the layout of the facilities obtained by the From to Chart (FTC) method and the Layout Design Program Algorithm method. (ALDEP). The researchers took this problem to study because the production process flow from Adelian convection is still not optimal due to the large number of alternating material flows that cause swelling in material handling costs, resulting in less effective and efficient work. The results of the study using the FTC method obtained that the distance for the movement of goods for the initial layout from the process starting to storage is 624 m. The distance of the movement of goods for the proposal layout from the start of the process to storage is 437 m. Therefore, there is a reduction in the distance between facilities from the start of the process to the storage of goods by 187 m. The results of the study using the ALDEP method could cost material handling costs of 30.01% from the comparison between OMH/month in the initial layout, which was Rp.26. 947,778 with OMH/month from the proposal layout, which was Rp. 18,861,310.8, so there was a decrease in OMH/month by Rp. 8,086,467.2.